Predictors of stress among a sample of Egyptian healthcare providers during the COVID-19 pandemic - Nermin Mahmoud Shaker (SpringerOpen, 2021)
Abstract Background The COVID-19 pandemic had a tremendous effect on people’s mental health. Healthcare workers were on the front lines in response to this crisis; therefore, they were among the most affected by the pandemic. The study aims to assess the stress perceived by healthcare workers and possible factors contributing to it, hoping that more efforts will be exerted to support the well-being of healthcare workers during public health emergencies. A cross-sectional study using an online survey was conducted. Data were collected from 118 healthcare professionals working with COVID-19 patients during the peak of the first wave of the COVID-19 pandemic. Results Most of the respondents (75.2%) scored much higher stress levels than average, and 19.5% had slightly higher levels of stress. Most respondents were afraid of infecting their family and close ones (77.1 %), and about half of the respondents were afraid of getting infected (47.5%). Regression analysis revealed that the only significant independent variable predicting developing higher stress levels among the participants was assigning them to tasks outside their specialty. Conclusions Healthcare workers are at high risk of developing mental health problems during public health emergencies. Their well-being is essential for the quality of services they provide. More efforts are needed to ensure the well-being of healthcare workers and to prepare them for such emergencies. Preparing healthcare workers before redeployment through training and providing PPEs will help to reduce the negative impact of the COVID-19 pandemic on their physical and mental health.